The tree of life - Estes, Douglas, (Themes in Biblical Narrative;, 2020)
"The tree of life is an iconic visual symbol at the edge of religious thought over the last several millennia. As a show of its significance, the tree bookends the Christian canon; yet scholarship has paid it minimal attention in the modern era. In The Tree of Life a team of scholars explore the origin, development, meaning, reception, and theology of this consequential yet obscure symbol. The fourteen essays trek from the origins of the tree in the texts and material culture of the ancient Near East, to its notable roles in biblical literature, to its expansion by early church fathers and Gnostics, to its rebirth in medieval art and culture, and to its place in modern theological thought. Contributors are: Amy L. Balogh, James H. Charlesworth, Charles L. Echols, Mark Edwards, Douglas Estes, Christopher Heard, Dustyn Elizabeth Keepers, Ty David Kieser, Peter T. Lanfer, Jutta Leonhardt Balzer, G. Ronald Murphy, S.J., William R. Osborne, Ken M. Penner, Pippa Salonius, Carl B. Smith II, Beth M. Stovell, Daniel J. Treier".